Pengaruh Kebijakan Utang Kinerja Keuangan dan Umur Perusahaan Terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Properti dan Real Estate yang Terdaftar di BEI Periode 2017-2021 - Desi Melyani; Nina Shabrina (Jurnal Manajemen & Pendidikan [JUMANDIK], 2025)
This research aims to determine the influence of Debt Policy (DAR), Financial Performance (ROA), and Company Age on Company Value in Property and Real Estate Sector Companies on the Indonesia Stock Exchange (BEI) for the 2017-2021 period. This research uses associative quantitative methods with the data analysis methods used are descriptive statistical tests, model estimation, model determination, classical assumption tests, panel data regression, hypothesis testing and coefficient of determination tests with the help of the E-Views Serie 12 program, with a significance level of 0 .05 (5%) and the data source used is secondary data. The research results show that partially DAR has a positive and significant effect on Company Value which has a value of tcount > ttable (3.194114 > 2.0129) and a significance level of (0.0029 < 0.05). ROA has no significant influence on Company Value which has a value of tcount < ttable (1.817774 < 2.0129) and a significance level of (0.0772 > 0.05). Company age has a positive and significant effect on company value which has a value of tcount < ttable (2.152643 > 2.0129) and a significance level of (0.0379 < 0.05). The variables DAR, ROA, and Company Age together (simultaneously) have a significant effect on the Company Value of property and real estate sector companies listed on the IDX for the 2017-2021 period with the value Fcount > Ftable (24.30597 > 2.81) and the value Prob (F -Statistics) 0.000000 is smaller than the specified significance level (0.000000 < 0.05). The results of the coefficient of determination test obtained an R-squared value of 0.887426 or 88.74% of the independent variables were able to explain the influence on the dependent variable and the remaining 11.26% was influenced by other variables not examined in this research.